1994
DOI: 10.1159/000147553
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Somatomammotroph Cells in Lactating Goats <i>(Capra hircus)</i> by Fluorescence and Immunogold Techniques

Abstract: The occurrence and ultrastructural morphology of somatomammotroph cells, in the anterior pituitary tissue of the goat, is studied using fluorescence microscopic double staining and two methods of double immunogold staining combined with electron microscopy. Under the fluorescence microscope numerous monohormonal cells, either mammotroph cells (prolactin, PRL, cells) or somatotroph cells (growth hormone, GH, cells) are observed, but cells containing both hormones (somatomammotroph or SMT cells) are scarce. SMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Such PRL-and GH-containing bihormonal cells have been identified in the human (12), bovine (13), goat (14), sheep (15), bat (16), rat (17), mouse (18), and musk shrew (19) anterior pituitary gland. To our knowledge, this is the first report of the existence of mammosomatotrophs within the avian pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such PRL-and GH-containing bihormonal cells have been identified in the human (12), bovine (13), goat (14), sheep (15), bat (16), rat (17), mouse (18), and musk shrew (19) anterior pituitary gland. To our knowledge, this is the first report of the existence of mammosomatotrophs within the avian pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian mammosomatotrophs, GH and PRL were reported to occur both inside the same secretory granules (12) and in separate granules (22). In previous immunohistochemical studies, the occurrence of mammosomatotrophs was reported to be rare in the lactating goat (14), whereas in sheep, mammosomatotrophs comprised 0.15% of all pituitary cells (15). Mammosomatotrophs formed 5.6 -9.6% of all pituitary cells obtained from virgin, late lactating, and postweaning rats (2) in reverse hemolytic plaque assays, and their relative proportions did not significantly change at the above physiological states.…”
Section: Turkey Mammosomatotrophsmentioning
confidence: 98%
“…Studies of pituitary cells have shown that GH and PRL cells are also derived from a common progenitor cell (Borrelli et al, 1989). MS cells are adenohypophyseal endocrine cells, which contain both GH and PRL, and are widely distributed in mammals (Fumagalli and Zanini, 1985;Nikitovitch-Winer et al, 1987;Asa et al, 1988;Ishibashi and Shiino, 1989a, b;Porter et al, 1990;Sá nchez et al, 1994;Vidal et al, 1995;Gómez et al, 1999) and hen (Ramesh et al, 1998). In fish, MS cells have only been reported during pituitary development in Sparus aurata by light microscopic immunocytochemistry (Villaplana et al, 2000).…”
mentioning
confidence: 99%